Developing Frameworks for Studies on Sedimentary Fluxes and Budgets in Changing Cold Environments - Beylich, Achim; Lamoureux, Scott; Decaulne, Armelle (Quaestiones Geographicae, 2011)
Geomorphic processes that are responsible for the transfer of sediments and landform change are highly dependent on climate and vegetation cover. It is anticipated that climate change will have a major impact on the behaviour of Earth surface systems and that the most profound changes will occur in high-latitude and high-altitude cold environments. Collection, comparison and evaluation of data from a range of different high-latitude and high-altitude cold environments are required to permit greater understanding of sedimentary fluxes in cold environments. The focus of the I.A.G./A.I.G. SEDIBUD (Sediment Budgets in Cold Environments) Programme is the analysis of source-to-sink fluxes and sediment budgets in changing cold environments. Establishing contemporary sediment fluxes in a diversity of cold environments will form a baseline for modelling. At a minimum, baseline information from defined SEDIBUD test sites must consist of measures of mean annual precipitation, stream discharge, suspended load, conductivity/TDS and dominant catchment processes. Reports from ongoing studies on sedimentary fluxes and budgets in three selected study sites in Arctic Canada, sub-Arctic Iceland and sub-Arctic Norway are presented and discussed in the context of effects of climate change on process rates and sediment budgets in sensitive cold environments. Comparable datasets and coordinated data collection and data exchange will be of use for the individual studies at the different study sites. In addition, comparable data sets and data exchange will help to improve our understanding of existing relationships between contemporary climate and sedimentary fluxes and will enable larger-scale integrated investigations on effects of climate change in changing cold environments.